Keanekaragaman Jamur Makroskopis di Danau Perintis Provinsi Gorontalo Sebagai Sumber Belajar Biologi - Herinda Mardin; Ilyas H. Husain (Peneliti.net, 2023)
Learning biology by learning directly with direct objects makes students’ learning experience more real. This study aimed to create valid and appropriate fungi learning resources based on the results of research on macroscopic fungi diversity in Perintis Lake, Gorontalo province. This research is a qualitative descriptive study, by making student worksheets (LKPD) based on PBL (Problem-Based Learning) based on the results of research on the diversity of macroscopic fungi found in Perintis Lake. The flow of this research is to make learning resources in the form of worksheets based on the results of research on the types of macroscopic fungi in Lake Perintis, then validate the learning resources with 4 (four) validators. Furthermore, data validation results from 4 (four) validators are calculated by analysis of the Content Validity Ratio (CVR) and CVI (Content Validity Index). The results of this study based on data analysis and calculation of the validation results from the four validators on learning resources in the form of LKPD which have been carried out show that each criterion obtains a CVR value of 1.00 with a valid statement, while the average value of each criterion is obtained through CVI calculations show that LKPD with validation results is valid with a CVI value of 1.00. The conclusion of this study is that biology learning resources in the form of student worksheets (LKPD) based on observations of macroscopic fungi found in the Perintis lake of Gorontalo Province are declared valid with a CVI value of 1.00 and is suitable for use as a source of learning biology on fungi class X SMA.